Emotional intelligence, spiritual intelligence and perception of God in association with coronary heart disease - Jahanzad, Sarvenaz; Jahanzad, Sara; Bakhshandeh, Hooman (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present research was to compare coronary heart disease patients and those without the disease in the scales of emotional intelligence, spiritual intelligence and perception of God. The present study is a case-control study. The statistical population of this research is all adults aged 45 years and older who are candidates for coronary angiography referred to Shahid Rajaei Cardiovascular Hospital in Tehran who have been selected by sampling method at convenience. The sample consisted of 68 patients (36 coronary heart disease patients and 32 non-coronary heart disease patients). We used Questionnaires of Bradbury and Greaves’s emotional intelligence, King’s spiritual intelligence and Lawrence’s perception of God to measure the scales. Findings showed that two groups of coronary heart patients and non-coronary heart patients in all subscales of emotional intelligence (self-awareness, self-management, social awareness and relationship management), all subscales of spiritual intelligence (critical existential thinking, personal meaning production, Transcendent awareness and expansion of consciousness) and the total score of spiritual intelligence are significantly different (P <0.05). This is while there was no significant difference in the total score of perception of God and all subscales of perception of God except the challenge subscale (P> 0.05). Differences in the results of the two groups of coronary heart patients and non-coronary heart patients show that emotional intelligence and spiritual intelligence can be effective in the health and recovery of coronary heart patients.